Implementation of Story Mapping Strategy to Improve Students’ Reading Comprehension of Narrative Text - Windy Kurnia Dewi; Juliana Juliana (Edumaspul: Jurnal Pendidikan, 2025)
This research aimed to improve eighth-grade students’ understanding of narrative text using the Story Mapping Strategy at SMP PAB 8 Sampali. The research employed Classroom Action Research (CAR), conducted over two cycles that included planning, execution, observation, and reflection phases. Data collection methods comprised multiple-choice assessments, observation checklists, interviews, documentation, and field notes. Findings indicated consistent improvement in students’ reading comprehension throughout the process, with average scores rising from 42.32 on the pre-test to 64.82 after the first cycle and reaching 83.04 following the second cycle. The use of the Story Mapping Strategy proved effective in aiding students to identify the main ideas and supporting details within narrative texts, while also fostering increased participation in the classroom. Consequently, this approach can be regarded as both engaging and successful in advancing students’ understanding of narrative reading material.